The role of lateral-entry Steinmann pins in the treatment of pediatric supracondylar humerus fractures - Weinberg, Jacob (Springer Berlin Heidelberg, 2010)
PURPOSE: Loss of pin fixation in supracondylar fractures can occur with failure to achieve bicortical fixation. Bicortical fixation may be challenging for those pins that attempt to penetrate the diaphyseal cortex, where the bone is thick. Lateral-entry Steinmann pins may allow for better penetration through cortical bone because they are more rigid than typical Kirschner wires. METHODS: A retrospective review of 16 children with type III supracondylar fractures treated by a single surgeon using Steinmann pins was undertaken. The average age at presentation was 6 years. Following closed reduction, all fractures were maintained with three lateral-entry pins. At least one Steinmann pin was placed in the lateral column of the distal humerus in each pin construct. RESULTS: Follow-up radiographs indicated a mean Baumann’s angle of 72.9° (range 64°–82°). There was no statistically significant change in the Baumann’s angle or axial alignment at final follow-up. All but one fracture healed in an anatomic position on the lateral view. CONCLUSIONS: Steinmann pins placed through a lateral-entry point are effective in controlling the reduction of high-grade supracondylar fractures. The fixation is excellent and avoids potential ulnar nerve complications of medial entry.